Evolution : scripture and nature say yes! - Lamoureux, Denis (2016)
In Evolution: Scripture and Nature Say Yes, theologian and scientist Denis O. Lamoureux reviews several options for embracing biblical Christianity and findings of science, including biological evolution. Holding to a high view of Scripture alongside an expert appreciation for scientific discovery, Lamoureux further outlines a way to understand passages referring to the natural world in the Bible and also demonstrates how modern science can point toward God. --
Trapped in "either/or" thinking -- Opening God's two books -- Terms that begin to free us - - Intelligent design and the book of God's works -- Ancient science and the book of God's words -- Moving beyond the "evolution" vs. "creation" debate -- Galileo and God's two books -- The religious evolution of Darwin -- Let the students speak!.
Includes bibliographical references.
Keywords: Evolution -- Religious aspects -- Christianity; Religion and science